Analysis of Career Development of Civil Servants in the Regional Secretariat of Bintuni Bay Regency - Penus Iba; Wilson Bogar; Sisca B. Kairupan (Technium Social Sciences Journal, 2025)
The purpose of this study was to determine and analyze how the career development of civil servants (PNS) and the factors that influence the career development of civil servants applied in the regional secretariat of the Bintuni Bay Regency. This research uses descriptive qualitative methods. The results showed that career development for the State Civil Apparatus (ASN) within the scope of the regional government of Bintuni Bay Regency has been running well in accordance with applicable rules and regulations by fulfilling the criteria and requirements in career development. Factors that influence the career development of ASN within the scope of the Bintuni Bay Regency local government are that the education and training dimension for ASN has been carried out well, although budget issues are a burden in maximizing education and training, the promotion dimension has been carried out well by staffing parties in accordance with the prerequisites of education, rank and class, work performance, responsibility, integrity and applicable provisions by adhering to the principles of transparency, accountability and accessible to all parties in the promotion process. While the mutation dimension, in accordance with the expertise and skills possessed by the ASN concerned, aims for promotion to a higher position level, in accordance with the prerequisites and applicable provisions.